Klebsiella pneumoniae Isolated from Subclinical Mastitis Milk of Etawah Crossbreed Goat - Clara Ajeng Artdita; Fajar Budi Lestari; Achmad Fauzi; Erian Pemila Ayu Tanzila (Jurnal Sain Veteriner, 2018)
Klebsiella spp. is a common bacteria causing mastitis. Klebsiella pneumoniae and Klebsiella varicola is the most infected Klebsiella spp in the dairy farm. This study used 16 milk samples from 8 lactation goats in Sahabat Ternak farm, Sleman, Yogyakarta. Samples were tested by california mastitis test (CMT) reagent to determine the mastitis status, inoculated on blood agar (BA) then on Mac Conkey Agar (MCA) as a selective media for Gram negative bacteria. The colonies from BA and MCA were stained by Gram staining to determine Gram-positive or Gram-negative bacteria and its cell morphology. The colonies from MCA were identified by biochemical tests such as sugar fermentation tests (glucose, lactose, maltose, and saccharose), arginine, ornithine decarboxylase, indole, citrate, urea hydrolysis (Christensen’s method), lysin and malonate. The result of mastitis test showed 5 goats were positive result and 3 samples were negative. Bacterial staining showed 2 samples were Gram-negative, rods and the others were Gram-positive, coccus. The samples with rods shapes were continued by biochemical tests. The characterization result of biochemical test indicated that the rods shapes bacteria were Klebsiella pneumoniae. These bacteria identification conducted in Laboratorium Preklinis Program Studi Kesehatan Hewan, Sekolah Vokasi Universitas Gadjah Mada and the result confirmation using positive control of  Klebsiella pneumoniae conducted in Balai Laboratorium Kesehatan Yogyakarta. These results showed that milk from Etawah crossbreed goat was infected by Klebsiella pneumoniae.